Analysis of Educational Technology Approaches in Supporting Health Services at College Clinics - Undap, Tiersa Reinie (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
Educational technology is a growing area of interest, including healthcare management in higher education. This study aims to evaluate the role of educational technology in improving health service management in college clinics, with a focus on the Universitas Negeri Manado Clinic. The research method used was a qualitative approach with data collection techniques including in-depth interviews, direct observation, and documentation. Data were analyzed using the triangulation method to identify key themes and in-depth interpretation of the influence of educational technology on health services. The results showed that the implementation of educational technology in college clinics can improve the efficiency and effectiveness of health services. Information technologies such as electronic medical record management systems and e-learning platforms have helped to improve the process of planning, implementing and evaluating health services. However, there are challenges in terms of system integration and additional training needs for staff. This study found that while educational technology provides significant benefits, its successful implementation is highly dependent on infrastructure readiness and user skills. Suggestions for improvement include increasing technology training for staff, updating hardware and software, and strengthening evaluation procedures to ensure that technology can be optimally used to improve the quality of health services.